Comparative Hydrochemical Evaluation of Water At Ilokun Village and Ado-Ekiti Metropolis, Southwestern Nigeria. - Ojo, Talabi Abel; Akinola, Oyedele Akintunde; Ayodele, Ajayi Christopher; Olatayo, Afolagboye Lekan; Amos, Ojo Abayomi; Kolawole, Popoola (European Journal of Applied Sciences, 2021)
This study focused on comparative hydrochemical evaluation of water in Ado-Ekiti metropolis and Ilokun Village (where there is an open refuse dump), Southwestern Nigeria. Fifteen groundwater samples from Ado-Ekiti Metropolis, four groundwater samples and three stream water samples from Ilokun village were collected and analyzed for physico-chemical parameters. In-situ parameters (Temp. (°C), EC (µS/cm), pH and TDS (mg/L)) were measured using Multi-parameter Testr™ 35 Series S/NO: 1382654. Major cations and anions were determined employing Atomic Absorption Spectrometer and Colorimetric methods respectively. The pH revealed that water in Ado-Ekiti was slightly acidic to alkaline while that of Ilokun village was alkaline. The order of major ions concentrations in Ado-Ekiti metropolis and Ilokun village were Mg<K<Na<Ca and Mg<K<Ca<Na and HCO3<Cl<SO4<NO3 and Cl<HCO3<SO4<NO3 respectively. EC (µS/cm) values of all sampled water were <1000 except in a location at Ilokun village close to the refuse dump signifying local anthropogenic contamination. CaCl (54.55%) was the dominant water type and all were Ado-Ekiti groundwater. CaHCO3 (9.10 % Ado-Ekiti groundwater, 9.10% Ilokun water), NaCl (13.60 % Ilokun water), CaNaHCO3 (4.55% Ado-Ekiti groundwater) and CaMgCl (4.55% Ado-Ekiti groundwater, 4.55% Ilokun water) represent minor water types. The water chemistry in the study area may have modified from weathering materials derived from the underlying bedrocks. Based on graphical evaluation and estimated irrigation parameters, both Ado-Ekiti groundwater and Ilokun water were suitable for irrigation purposes. Hydrochemical parameters and all estimated irrigation parameters showed marked quality differences with respect to Ado-Ekiti groundwater and Ilokun water.